Exfoliation of clay layers in polypropylene matrix using potassium succinate-g-polypropylene as compatibilizer - Rama, Mallikarjuna Shroff; Neppalli, Ramesh; Chellaswamy, Ramesh; Swaminathan, Sivaram (Composites Science and Technology, 2010)
The efficiency of potassium succinate-g-polypropylene (KPPSA) as compatibilizer for the dispersion of clay in a high molecular weight polypropylene during melt mixing for the preparation of nanocomposites was evaluated and compared with maleic anhydride-g-polypropylene (PPMA). Nanocomposites were prepared by direct melt mixing and by masterbatch methods and the structure obtained was characterized by WAXD and TEM. The exfoliation and better dispersion of the organoclay was observed with KPPSA than PPMA. The dispersion of clay was found to be dependent on the method of preparation, type and the amount of compatibilizer used. The dispersion was better when the nanocomposites were prepared by two step masterbatch route than the single step direct mixing method. Flexural moduli and crystallization behavior were studied and correlated with the dispersion of organoclay in the PP matrix. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: differential scanning calorimetry; Mechanical property; Nano composites; Nanoclays; polypropylene

Synthesis and characterization of cholesteric thermotropic liquid crystalline polyesters based on isosorbide - Chavan, Nayaku (Materials Sciences and Applications, 2011)
Generally main chain cholesteric thermotropic liquid crystalline polymers are prepared form chiral dia-cid or diol monomer. But these monomers are costly. Isosorbide is chiral cycloaliphatic diol accessible from renewable resources in the form of pure enantiomers. Thus it is used to synthesize main chain cholesteric thermotropic liquid crystalline polymers. Incorporation of phenyl hydroquinone into the backbone of the main chain frustrates chain pack-ing, thus lowering the crystallinity and depressing the melting point below the degradation temperature, also improves the solubility due to disruption of packing and maintains the mechanical and thermal performance. Results: Optical microscopy study reveals that more than 50% of isosorbide content with phenyl hydroquinone and terephthalic acid showed “yellow iridescent oily streaks” with a background of mosaic/marble texture. These are the typical textures of cholesteric liquid crystalline phase. Copolyesters based on phenyl hydroquinone, isosorbide and terephthalic acid are soluble in aprotic solvents like N,N-dimethylacetamide (DMAC), dimethyl sulfoxide (DMSO), N,N-dimethylformamide (DMF), and N-methyl-2-pyrrolidone (NMP). Solubility increases with the content of isosorbide percent. Thermal stabil-ity of all copolyesters was more than 300˚C on the basis of 10 wt% loss. Conclusions: It was found that main chain cholesteric thermotropic liquid crystalline polymers can be prepared form chiral cycloaliphatic diol such as isosorbide. Main chain cholesteric thermotropic liquid crystalline polyesters are prepared from phenyl hydroquinone, isosorbide and terephthalic acid showed thermal stability more than 300˚C. Main chain cholesteric thermotropic liquid crystalline polymers are soluble in aprotic solvents like DMAC, DMSO, DMF and NMP
Keywords: Cholesteric; Crystallinity; differential scanning calorimetry; Inherent Viscosity; Liquid Crystalline Polymers; Optical Microscopy; Solubility and Solution Polycondensation; Thermo Gravimetric Analysis; thermotropic; Wide Angle X-Ray Diffraction

Polyproline fold-In imparting kinetic stability to an alkaline serine endopeptidase - Rohamare, Sonali B.; Dixit, Vaishali; Nareddy, Pavan Kumar; Sivaramakrishna, D.; Swamy, Musti J.; Gaikwad, Sushama M. (Biochimica Et Biophysica Acta-Proteins and Proteomics, 2013)
Polyproline II (PPII) fold, an unusual structural element was detected in the serine protease from Nocardiopsis sp. NCIM 5124 (NprotI) based on far UV circular dichroism spectrum, structural transitions of the enzyme in presence of GdnHCl and a distinct isodichroic point in chemical and thermal denaturation. The functional activity and conformational transitions of the enzyme were studied under various denaturing conditions. Enzymatic activity of NprotI was stable in the vicinity of GdnHCl upto 6.0 M concentration, organic solvents viz, methanol, ethanol, propanol (all 90% v/v), acetonitrile (75% v/v) and proteases such as trypsin, chymottypsin and proteinase K (NprotI:protease 10:1). NprotI seems to be a kinetically stable protease with a high energy barrier between folded and unfolded states. Also, an enhancement in the activity of the enzyme was observed in 1 M GdnHCl upto 8 h, in organic solvents (75% v/v) for 72 h and in presence of proteolytic enzymes. The polyproline fold remained unaltered or became more prominent under the above mentioned conditions. However, it diminished gradually during thermal denaturation above 60 degrees C. Thermal transition studies by differential scanning calorimetry (DSC) showed scan rate dependence as well as irreversibility of denaturation, the properties characteristic of kinetically stable proteins. This is the first report of PPII helix being the global conformation of a non structural protein, an alkaline serine protease, from a microbial source, imparting kinetic stability to the protein. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: Conformation; differential scanning calorimetry; Kinetic stability; Nocardiopsis sp.; Polyproline fold; Serine protease

Synthesis and characterization of well-defined random and block copolymers of epsilon-caprolactone with l-lactide as an additive for toughening polylactide: Influence of the molecular architecture - Deokar, Megha D.; Idage, Susheela B.; Idage, Bhaskar B.; Sivaram, Swaminathan (Journal of Applied Polymer Science, 2016)
Well-defined multiarmed star random and block copolymers of epsilon-caprolactone with l-lactide with controlled molecular weights, low polydispersities, and precise numbers of arms were synthesized by the ring-opening polymerization of respective cyclic ester monomers. The polymers were characterized by H-1-NMR and C-13-NMR to determine their chemical composition, molecular structure, degree of randomness, and proof of block copolymer formation. Gel permeation chromatography was used to establish the degree of branching. Star-branched random copolymers exhibited lower glass-transition temperatures (T-g's) compared to a linear random copolymer. When the star random copolymers were melt-blended with poly(l-lactic acid) (PLA), we observed that the elongation of the blend increased with the number of arms of the copolymer. Six-armed block copolymers, which exhibited higher T-g's, caused the maximum improvement in elongation. In all cases, improvements in the elongation were achieved with no loss of stiffness in the PLA blends. (c) 2015 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2016, 133, 43267.
Keywords: biodegradable; copolymers; differential scanning calorimetry; mechanical properties; ring-opening polymerization